What is the relations between dysgeusia and alterations of the nutritional status? A metanarrative analysis of integrative review - Dellafiore, Federica; Bascapè, Barbara; Caruso, Rosario; Conte, Gianluca; Udugampolage, Nathasha Samali; Carenzi, Laura; Arrigoni, Cristina (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Dysgeusia is  an altered or damaged tasting perception of a multifactorial etiology, from polypharmacy, infections to chemotherapy and radiotherapy. Approximately 5% of the population suffer from a diminished taste sensation, which unfortunately remains underestimated by the affected person, creating the conditions for a dramatic underestimation of the incidence of the symptom. The aim of this study is to summarize the evidences present in literature on the relations between Dysgeusia and alterations of the nutritional statusMethods: an integrative review with metanarrative analysis of the articles included was carried out in August 2020. PubMed, Scopus, Embase and CINAHL databases were examined with keywords and methodological strings. PRISMA flow-chart along with a qualitative evaluation grid (JBI-QARI) were applied in the selection of the studies with a time limitation to the last ten years.Results: 10 articles resulted from the literature review process were divided into two macro-categories. Eight articles reported dysgeusia linked to weight loss. The second macro-category showed two studies relating to dysgeusia in patients with altered nutritional status associated with body weight gain.Conclusions: this review represents an initial contribution to summarize the best evidence and knowledge in relation to dysgeusia, with the aim of enabling the identification and treatment of this symptom and facilitating targeted educational interventions.